A Comparison of the Utilization of Carbon Nanopowder and Activated Carbon as Counter Electrode for Monolithic Dye-Sensitized Solar Cells (DSSC) - Zaky Mubarak; Natalita Maulani Nursam; Shobih Shobih; Jojo Hidayat; Dahlang Tahir (Jurnal Elektronika dan Telekomunikasi, 2018)
Monolithic design is one of the most promising dye-sensitized solar cell (DSSC) architectures to develop, because it allows the elimination of one conductive substrate and offers the possibility for printing layer-by-layer of the materials that made up its structure. In this study, titanium dioxide-based monolithic type DSSCs were fabricated on a single fluorine-doped transparent oxide coated glass with TiO2 as photoanode and porous ZrO2 as spacer. The type of the carbon material used as the composite paste for the counter electrode was varied to see the effect on the solar cell efficiency. Four-point probes measurement revealed that the resistivity of the carbon layer synthesized using activated carbon exhibited slightly higher conductivity with a sheet resistance of 10.70 Ω/sq and 11.09 Ω/sq for activated carbon and carbon nanopowder, respectively. The efficiency of DSSC that uses activated carbon as counter electrode was higher (i.e. 0.221%) than the DSSC with carbon nanopowder (i.e. 0.005%). The better performance of DSSC with activated carbon as a counter electrode was due to its better conductivity and higher surface area compared to those of carbon nanopowder.